High Level Forum of Climate-Smart Agriculture (CSA) Stakeholders in West Africa - CGIAR Research Program on Climate Change, Agriculture and Food Security (2015)
Economic Community of West African States (ECOWAS) organized a high-level forum of 15 to 18 june in Bamako with all west african stakeholders of Climate Smart Agriculture (CSA).